Carbonaceous matter in glacier at the headwaters of the Yangtze River: Concentration, sources and fractionation during the melting process - Hu, Zhaofu; Kang, Shichang; He, Xiaobo; Yan, Fangping; Zhang, Yulan; Chen, Pengfei; Li, Xiaofei; Gao, Shaopeng; Li, Chaoliu (Journal of Environmental Sciences, 2020)
Carbonaceous matter has an important impact on glacial retreat in the Tibetan Plateau, further affecting the water resource supply. However, the related studies on carbonaceous matter are still scarce in Geladaindong (GLDD) region, the source of the Yangtze River. Therefore, the concentration, source and variations of carbonaceous matter at Ganglongjiama (GLJM) glacier in GLDD region were investigated during the melting period in 2017, which could deepen our understanding on carbonaceous matter contribution to glacier melting. The results showed that dissolved organic carbon (DOC) concentration of snowpit samples (283 +/- 200 mu g/L) was much lower than that of precipitation samples (624 +/- 361 mu g/L), indicating that large parts of DOC could be rapidly leached from the snowpit during the melting process. In contrast, refractory black carbon (rBC) concentration measured by Single Particle Soot Photometer of snowpit samples (4.27 +/- 3.15 mu g/L) was much higher than that of precipitation samples (0.97 +/- 0.49 mu g/L). Similarly, DOC with high mass absorption cross-section measured at 365 nm value was also likely to enrich in snowpit during the melting process. In addition, it was found that both rBC and DOC with high light-absorbing ability began to leach from the snowpit when melting process became stronger. Therefore, rBC and DOC with high light-absorbing ability exhibited similar behavior during the melting process. Based on relationship among DOC, rBC and K+ in precipitation, the main source of carbonaceous matter in GLJM glacier was biomass burning during the study period. (c) 2019 The Research Center for Eco-Environmental Sciences, Chinese Academy of Sciences. Published by Elsevier B.V.